Penerapan Strategi Project Based Learning di SDS Islam Azizi - Arlina, Arlina; Nasution, Khairy Fitra; Siahaan, Mariadina; Siregar, Nabila Ufaira (TSAQOFAH, 2025)
Project-Based Learning (PBL) has become an effective teaching strategy in education, focusing on the development of critical thinking, collaborative skills, and problem-solving in students. This study aims to analyze the steps in implementing PBL in the classroom, identify the benefits and challenges in its implementation, and assess the impact of PBL on students' collaboration and problem-solving skills. By adopting this approach, students engage in projects that are relevant to real-life situations, allowing them to apply academic knowledge in a contextual manner. The findings indicate that PBL enhances student motivation and engagement, although it requires significant time and resources. This research is expected to provide guidance for educators in effectively implementing PBL and contribute to policymakers in developing curricula that are more adaptable to the needs of contemporary education.